School of English for Political Scientist - I. A. Mazaeva (Vestnik MGIMO-Universiteta, 2014)
Department of English Language № 7 was founded in 2001. Originally its teaching staff included the specialists of the Department of English Language Chair. Since its inception, the chair has paid particular attention to the introduction of innovative teaching methods and techniques. This is realized by a competence-based and personalized approach, implemented by I.A. Winter as well as and cognitive and communicative approaches to education. The development of intellectual, communicative and personal qualities of students and the teachers is the main goal of the educational process, achieved by the teaching staff witch the use of innovative competence-oriented teaching techniques, and types of assessment at the different levels of education.